Paranasal Augmentation With Composite Graft Transfer in Overresection of Alar Base and Nostril Contracture. Issue 2 (February 2021) - Yen, Cheng-I; Chang, Chun-Shin; Chen, Hung-Chang; Yang, Shih-Yi; Chang, Shu-Yin; Yang, Jui-Yung; Chuang, Shiow-Shuh; Hsiao, Yen-Chang
Abstract : Background: Many Asian patients desire a narrower nasal base with less flaring of the alar lobules. However, patients who underwent multiple rhinoplasty surgeries with nostril contracture or an overreduction of the alar base may experience nostril contracture and deformity, which may lead to further airway obstruction. We present a technique that combines paranasal augmentation with composite chondrocutaneous graft transfer to overcome this problem. Methods: Nine patients underwent composite chondrocutaneous graft transfer to the soft triangle or alar base combined with paranasal augmentation using preshaped porous polyethylene implants to correct nostril contracture and airway obstruction between September of 2014 and May of 2018. Preoperative and postoperative alar base distances and cross-sectional areas of the nostrils were measured and compared. Results: The average thickness of paranasal augmentation was 5.5 mm (range, 4.0–7.0 mm). Eighteen composite grafts were located over the soft triangle (n = 3) and the alar base (n = 15). The average number of composite grafts for each person was 2 (range, 1–4). All composite grafts survived totally or partially, and no graft failed. The average follow-up was 10.9 months (range, 3–28 months). The alar base increased 13.9% (range, 2.2%–23.9%), and the nostril area increased an average of 78.1% (range, 4.5%–316.8%) postoperatively. Patients had satisfactory aesthetic and functional outcomes. Conclusions: Combining paranasal augmentation and composite graft transfer increased the cross-sectional area of the external valve and improved nostril contracture and airway obstruction after the overresection of the alar base or nose contracture after multiple rhinoplasty surgeries. Abstract : Supplemental digital content is available in the text.